Respostas
respondido por:
6
Olá!!
Resolução!!
x = - 1, y = - 4 , basta substitui na expressão
= x² + 2xy + y²
= ( - 1 )² + 2 • ( - 1 ) • ( - 4 ) + ( - 4 )²
= 1 + 2 • 4 + 16
= 1 + 8 + 16
= 9 + 16
= 25
R = 25
Espero ter ajudado!
Resolução!!
x = - 1, y = - 4 , basta substitui na expressão
= x² + 2xy + y²
= ( - 1 )² + 2 • ( - 1 ) • ( - 4 ) + ( - 4 )²
= 1 + 2 • 4 + 16
= 1 + 8 + 16
= 9 + 16
= 25
R = 25
Espero ter ajudado!
respondido por:
2
Substituindo os valores dados na expressão:
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás